Uplift‐driven diversification revealed by the historical biogeography of the cockroach Cryptocercus Scudder (Blattodea: Cryptocercidae) in eastern Asia. (27th June 2019) - Che, Yanli; Bai, Qikun; Deng, Wenbo; Liao, Shuran; He, Jiajun; Ho, Simon Y. W.; Wang, Zongqing
Abstract: Cryptocercus Scudder is a genus of wingless cockroaches, which spend their lives feeding within rotting wood in old‐growth montane forests. Their dispersal capability is likely to be limited because they depend on the succession of temperate forests, but their distribution exhibits intercontinental disjunctions. Although the natural history and conservation biology of the North American species of the genus have received much attention, the evolution of the eastern Asian lineages remains enigmatic. To resolve the geographic patterns and evolutionary history of Cryptocercus in eastern Asia, we analysed genetic data of species from China (27 species), Korea (one species) and the Russian Far East (one species). We performed phylogenetic analyses of seven genes to infer the evolutionary relationships among species of Asian Cryptocercus . We then used Bayesian molecular dating to estimate the evolutionary timescale of the genus. Ancestral geographic distributions were reconstructed in rasp using statistical dispersal‐vicariance analysis and statistical dispersal‐extinction‐cladogenesis. Our maximum‐likelihood and Bayesian phylogenetic trees supported four major lineages of Cryptocercus, revealing a clear geographical pattern. The divergence of American and Asian lineages was inferred to have occurred 74.8 Ma (95% credibility interval: 51.1–103.8 Ma), with the diversification of Asian taxa beginning at 30.7 Ma (95% credibility interval: 22.9–40.3 Ma). The most recent common ancestor of Asian Cryptocercus taxa was inferred to have had a broad distribution in Asia. The uplift of the Qinghai‐Tibet Plateau in the Palaeogene and Neogene, along with climatic oscillations in the Quaternary, probably had substantial effects on the formation of the disjunction pattern in the Cryptocercus lineages found in the Hengduan Mountains and Qin‐Daba Mountains of China. We propose that the distribution of Cryptocercus has been strongly influenced by habitat fragmentation and subsequent allopatric speciation. Abstract : The divergence of American and Asian Cryptocercus was inferred to have occurred 74.8 Ma. The most recent common ancestor of Asian Cryptocercus taxa was inferred to have had a broad distribution in Asia. The distribution of Cryptocercus has been strongly influenced by habitat fragmentation and subsequent allopatric speciation.